The Relationship Between Cultural Sensitivity and Assertiveness in Nursing Students from Turkey - Kilic, Serap Parlar; Sevinc, Sibel (Sage Publications Inc, 2018)
Background: As foreigners live in and visit Turkey for various reasons, it is essential to provide culturally appropriate health care. Purpose: This study was conducted to determine the relationship between cultural sensitivity and assertiveness in university nursing students. Method: This descriptive, cross-sectional study was conducted at two universities in the cities of Kilis and Elaz, Turkey. The study sample consisted of 444 nursing students. Data collection tools included a questionnaire about participant sociodemographic characteristics, Chen and Starosta's Intercultural Sensitivity Scale, and the Rathus Assertiveness Scale. Results: The mean age of participants was 21.09 years. Most students (71.6%) were female and 34.7% of the students stayed at the hostel. Of the students, 44.4%, 27.5%, and 28.2% attended were the second-, third-, and fourth-year students, respectively. Participants were asked about problems related to caring for patients who speak different languages. The mean score for the Intercultural Sensitivity Scale was 89.42 +/- 13.55 and the total score for all students for the Assertiveness Scale was 112.64 +/- 15.61. We identified a positive relationship between total scores for the Intercultural Sensitivity Scale and the Assertiveness Scale (p < .001). There was relationship between cultural sensitivity and gender and want to work overseas; assertiveness and year of nursing education and want to work overseas. Conclusions: Nursing students at both schools had a moderate level of cultural sensitivity and assertiveness. It has been determined that as assertiveness level of the students increased, intercultural sensitivity of them also increased. Implications for Practice: Consequently, it is concluded that training as assertive and self-confident individuals during the nursing education of students has a contribution to making patient-specific and culture-sensitive care.
Keywords: cultural sensitivity; assertiveness; nursing students; Turkey